2010
DOI: 10.1063/1.3298693
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of ultrathin (2×2) Gd nanowires encapsulated in carbon nanotubes

Abstract: Using density-functional calculations, we investigate the structural and magnetic properties of ultrathin Gd and Gd-carbide nanowires (NWs) encapsulated in narrow carbon nanotubes (CNTs). The equilibrium geometry of an encapsulated (2 x 2) Gd-NW is markedly different from that of bulk Gd crystals. The charge-density analysis shows pronounced spin-dependent electron transfer in the encapsulated Gd-NW in comparison with that of Gd-carbide NWs. We conclude that Gd-CNT hybridization is primarily responsible for bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
(41 reference statements)
3
16
0
Order By: Relevance
“…Recently reported density functional theory (DFT) band structure calculation of the metallic AWs encapsulated in CNTs (AW@CNTs) suggested that there is a significant electron transfer from metallic AWs to CNT and that the electronic structure of AW@CNTs could not be explained as a simple superposition of neutral AW and CNTs. [18][19][20] To understand the basic properties of this new class of low-dimensional systems in CNTs (AW@CNTs) and to elucidate their electronic structure, it is crucial to investigate the interaction exerted between the encapsulated AW and the CNT.…”
Section: Introductionmentioning
confidence: 99%
“…Recently reported density functional theory (DFT) band structure calculation of the metallic AWs encapsulated in CNTs (AW@CNTs) suggested that there is a significant electron transfer from metallic AWs to CNT and that the electronic structure of AW@CNTs could not be explained as a simple superposition of neutral AW and CNTs. [18][19][20] To understand the basic properties of this new class of low-dimensional systems in CNTs (AW@CNTs) and to elucidate their electronic structure, it is crucial to investigate the interaction exerted between the encapsulated AW and the CNT.…”
Section: Introductionmentioning
confidence: 99%
“…[46]. Furthermore, there are other reports on the investigation of donor doping of SWCNTs by metals, such as Ti, Zn [405], Co, Ni [410], Fe [405,406,409], Mo [407], Gd [402,408], Eu [402], Cu [404], Ag [401] (Table 3). Figure 36 shows the structural models and band structures of the pristine SWCNTs with a chirality of (8,8) and the nanotubes filled with iron nanowires (Fe n @SWCNT), containing n = 5, 9 and 13 metal atoms in the cross section [406].…”
Section: Experimental Methodsmentioning
confidence: 97%
“…According to the data presented in reports on the experimental and theoretical investigations of the electronic properties of filled SWCNTs, the following substances have an electron donor effect on the nanotubes: molecules -organic molecules (tetrakis(dimethylamino)ethylene (TDAE) and tetrathiafulvalene (TTF) [48,356]) and organometallic molecules (Co(C 5 H 5 ) 2 , Co(C 5 H 4 C 2 H 5 ) 2 [47,399,400], Fe(C 5 H 5 ) 2 [50,260,262,263,265,267,399,400], Ce(C 5 H 5 ) 3 [51,269], M(C 5 H 5 ) 2 , M= V, Cr, Mn, Ni [399]) and simple substances -metals (Ag [46,293,294,296,315,365,401], Cu [293,295], Eu [272,402], Li, K [403], Ti, Zn, Co, Ni, Fe, Mo, Gd, Cu [402,[404][405][406][407][408][409][410]). …”
Section: Typical Donors Of Electrons and Methods Of Their Encapsulationmentioning
confidence: 99%
“…Because of their central hollow space, single‐wall carbon nanotubes (SWCNTs) have been demonstrated to encapsulate fullerenes and/or endohedral metallofullerenes to form the so‐called peapods 1. Experiments have shown that there are substantial changes in the wide range of properties of nanotubes upon encapsulation of fullerenes/metallofullerenes and even of metal nanowires 2, 3. For example, transport properties of several fullerene peapods have been shown to be completely different from that of hollow SWCNTs when they are used as channels of field‐effect transistors (FETs) 4.…”
Section: Introductionmentioning
confidence: 99%